PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN TENTANG SISTEM PEMERINTAHAN REPUBLIK INDONESIA MELALUI STRATEGI PEMBELAJARAN GALLERY OF LEARNING SISWA KELAS VI SD NEGERI 4 PANGKAL SAWOO PONOROGO - Supaji, Supaji (Educatio Vitae, 2016)
The research which is aimed to know the improvement of the results of the study in the topic of comprehending the governmental system of Republic of Indonesia through the method of Gallery of Learning towards 13 sixth graders of Pangkal Sawoo state Primary School in Ponorogo in semester II 2011-2012 academic year is a class act research which is conducted in 3 cycles consisting of 6 meetings. Each meeting consists of 2 X 35 minutes including the activities of planning, implementation, observation, and reflection. The data are taken by using test instruments, interviewing, distributing questionnaires and journals. The learning model of Gallery of Learning in improving the learning competence is noticed by the improvement of mean score which is 72.31 in cycle I: 77.69 in cycle II; and 81.15 in cycle III. Moreover, there is also the percentage improvement of the learning accomplishment in which it is only 76.92% in cycle I, then, it is improving into 84.62% in cycle II and 100% in cycle III. The research proves that the use of the learning model of Gallery of Learning in the process of learning is capable in  improving the learning competence in the subject of Citizenship Education especially, in the topic of “comprehending the governmental system of Republic of Indonesia.” Key Words: The results of the study, Gallery of Learning, Citizenship Education